A new species of Hisonotus (Siluriformes: Loricariidae) from Aripuanã river, Amazon basin, Brazil - Dias, Angelica C.; Silva, Gabriel S. C.; Oliveira, Claudio; Roxo, Fábio F. (Zootaxa, 2018)
A new species of Hisonotus from rio Juma, located at the right margin of the lower rio Aripuanã, rio Madeira basin is described. The new species is distinguished from its congeners mainly by a reddish-tipped premaxillary and dentary teeth, a V-shaped spinelet, three lateral plates in abdominal series, the coloration pattern of caudal fin with three transversal dark bars, and by morphometric characters.